Penyusunan Anggaran Per Unit Kerja Asosiatif Dengan Anggaran Berbasis Kinerja? - Andilo Tohom (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
The process of preparing government agency budget can not be separated from the proposed work plan and budget of the division in government agencies based on its duties and functions. Each proposed activities, outputs and budget required then compiled into the budget of upper unit up to the level of Ministries/Agencies/Government. Nevertheless, it should be referred to objectives to be achieved by the government. A proper understanding of the principle of 'money follow function